Pascal and the natural law - Lazzeri, Christian (Sententiae, 2000)
The article examines the problem of Pascal's attitude to the concept of natural law in the context of a new way of understanding politics. This way emerged after the skeptical crisis of the late 16th century, along with attempts to scientifically justify natural law, which was intended to become the backbone of a new type of society. Pascal subjected this justification to radical criticism. Yet it is difficult to classify Pascal's position, because, on the one hand, it falls behind the mainstream of modern political philosophy, and on the other hand, it opens the way to a non-legal analysis of politics. It is this analysis that constitutes an alternative to the constructions of philosophers who were committed to the concept of the social contract.